2022
DOI: 10.3389/fpsyt.2022.867091
|View full text |Cite
|
Sign up to set email alerts
|

The Problem and Potential of TMS' Infinite Parameter Space: A Targeted Review and Road Map Forward

Abstract: BackgroundRepetitive transcranial magnetic stimulation (rTMS) is a non-invasive, effective, and FDA-approved brain stimulation method. However, rTMS parameter selection remains largely unexplored, with great potential for optimization. In this review, we highlight key studies underlying next generation rTMS therapies, particularly focusing on: (1) rTMS Parameters, (2) rTMS Target Engagement, (3) rTMS Interactions with Endogenous Brain Activity, and (4) Heritable Predisposition to Brain Stimulation Treatments.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 109 publications
0
16
0
Order By: Relevance
“…However, with non-invasive brain stimulation, we often see this is not the case. Rather, an inverted U-shape curve indicates a “sweet spot” for much of plasticity induction (Caulfield and Brown, 2022 ). In fact, in many cases, more stimulation may reverse results, such as by doubling iTBS pulse numbers (Gamboa et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, with non-invasive brain stimulation, we often see this is not the case. Rather, an inverted U-shape curve indicates a “sweet spot” for much of plasticity induction (Caulfield and Brown, 2022 ). In fact, in many cases, more stimulation may reverse results, such as by doubling iTBS pulse numbers (Gamboa et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…The most common rTMS protocol is to apply 120% MT stimulation over the left DLPFC, making the typical stimulation intensity range relatively limited. Despite the group-level efficacy of this commonly used intensity, some researchers have pointed out that the dose-response curve of multiple TMS parameters follows an inverted U-shape with peak efficacy in the middle [ 49 ]. Others have suggested that using prospective E-field dosing would help to further reduce the dose variability at the cortical level by taking tissue composition and conductivity into consideration [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, nTMS parameters, such as stimulation intensity and timing, are usually adjusted based on peripheral functional responses when available, e.g., when stimulating the motor cortex to observe motor evoked potentials (MEPs) through electromyography [ 15 , 16 , 17 , 18 ]. When electroencephalography (EEG) is recorded in a simultaneous coregistration, a more effective nTMS outcome can be obtained by adjusting the stimulation parameters based on the cortico-cortical responses as mapped by nTMS–EEG [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%